Polish cities as a space of history in Boris Khersonsky’s Family archive - Vorontsova, Kristina (Studia Rossica Posnaniensia, 2024)
This article is focused on the so-called urban texts related to Poland with a special emphasis on the historical and geographical region of Galicia, which covers the territories of Red Ruthenia in Ukraine and Lesser Poland, and on their historical connotations as presented in Boris Khersonsky’s book of poetry Family archive (2006). Khersonsky is a Russian-speaking Ukrainian poet from Odesa, who has been awarded prestigious prizes for his literary work both in Ukraine and abroad. Family archive can be described as a sort of novel in verse about the tragic history of the 20th century told through the family history of the author himself. The main goal of this article is to analyze the specific spatial structure of the book in the context of geopoetics and places of memory with a special accent on Polish cities and towns. This territory is the quintessential locus of historical events connected to Eastern European Jewish heritage and the tragedy of the Holocaust. This paper seeks to reconstruct the image of Poland with all the connotations and cultural myths associated with its multicultural experience.